Intermolecular zero quantum coherences enable accurate temperature imaging in red bone marrow. Issue 1 (18th July 2014) - Davis, Ryan M.; Warren, Warren S.
<x xml:space="preserve">Abstract</x> Purpose Red bone marrow metastases are common in breast and prostate cancer patients, but those metastases are currently incurable. Recent developments show that hyperthermia could be a successful treatment for bone metastasis, but thermometry remains difficult or inaccurate in red marrow. Method The technique evaluated in this study measures the evolution frequency of intermolecular zero quantum coherences (iZQCs) between fat and water. The iZQC evolution frequency was mapped linearly to temperature. The temperature accuracy and coherence lifetime of the iZQC method were evaluated against other thermometry methods that are based on localized spectroscopy and multiple gradient echo imaging. Results The temperature coefficient (α) was 9.8 ± 0.7 ppb/°C with the iZQC method and 2 ± 7 ppb/°C with traditional localized spectroscopy. Conclusion Because the accuracy of thermometry is limited by the reproducibility of α between samples, iZQCs provide nearly a 10‐fold accuracy improvement in red marrow (0.7 ppb/°C for iZQCs versus 7 ppb/°C for localized spectroscopy.) The iZQC technique in this study will for the first time allow accurate and quantitative thermal imaging of red marrow. Magn Reson Med, 2014. © 2014 Wiley Periodicals, Inc. Magn Reson Med 74:63–70, 2015. © 2014 Wiley Periodicals, Inc.